2010
DOI: 10.1002/anie.201000449
|View full text |Cite
|
Sign up to set email alerts
|

Glandular Trichomes of Leucosceptrum canum Harbor Defensive Sesterterpenoids

Abstract: On the defense: Sesterterpenoid 1 and its 11‐dehydroxy derivative, which possess a unique C25 skeleton, have been isolated from the glandular trichomes of Leucosceptrum canum. They have potent antifeedant activities and inhibitory effects against pathogenic fungi, which suggest a role of sesterterpenoids in plant defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 13 publications
2
96
0
Order By: Relevance
“…To investigate the relative distribution of sesterterpenoids in GTs compared with various whole organs of L. canum, HPLC analysis was performed on extracts of GTs, whole leaves, young stems, and flowers. In addition to previously reported leucosceptroids A (1, t R = 27.3 min) and B (5, t R = 31.8 min) (Luo et al, 2010), a number of other peaks were also detected ( Figure 1). These were not observed previously, possibly due to sampling having been conducted at a different time of year.…”
Section: Sesterterpenoids Are Highly Enriched In L Canum Glandular Tsupporting
confidence: 70%
See 4 more Smart Citations
“…To investigate the relative distribution of sesterterpenoids in GTs compared with various whole organs of L. canum, HPLC analysis was performed on extracts of GTs, whole leaves, young stems, and flowers. In addition to previously reported leucosceptroids A (1, t R = 27.3 min) and B (5, t R = 31.8 min) (Luo et al, 2010), a number of other peaks were also detected ( Figure 1). These were not observed previously, possibly due to sampling having been conducted at a different time of year.…”
Section: Sesterterpenoids Are Highly Enriched In L Canum Glandular Tsupporting
confidence: 70%
“…Our previous study of L. canum identified two sesterterpenoids possessing a unique C 25 skeleton, the leucosceptroids A and B, and found these to be present in glandular trichomes (GTs) on surfaces of the aerial parts of the plant (Luo et al, 2010). This suggested that the biosynthesis of these sesterterpenoids was probably also accomplished in GTs, since terpenoids accumulating in these structures in other plant species have been previously reported to be formed in situ (McCaskill et al, 1992;Wagner et al, 2004;Wang et al, 2008;Xie et al, 2008;Schilmiller et al, 2009).…”
Section: Sesterterpenoids Are Highly Enriched In L Canum Glandular Tmentioning
confidence: 95%
See 3 more Smart Citations